The role of the “gut microbiota-mitochondria” crosstalk in the pathogenesis of multiple sclerosis - Tian, Huan; Huang, Dunbing; Wang, Jiaqi; Li, Huaqiang; Gao, Jiaxin; Zhong, Yue; Xia, Libin; Zhang, Anren; Lin, Zhonghua; Ke, Xiaohua (Frontiers in Microbiology, 2024)
Multiple Sclerosis (MS) is a neurologic autoimmune disease whose exact pathophysiologic mechanisms remain to be elucidated. Recent studies have shown that the onset and progression of MS are associated with dysbiosis of the gut microbiota. Similarly, a large body of evidence suggests that mitochondrial dysfunction may also have a significant impact on the development of MS. Endosymbiotic theory has found that human mitochondria are microbial in origin and share similar biological characteristics with the gut microbiota. Therefore, gut microbiota and mitochondrial function crosstalk are relevant in the development of MS. However, the relationship between gut microbiota and mitochondrial function in the development of MS is not fully understood. Therefore, by synthesizing previous relevant literature, this paper focuses on the changes in gut microbiota and metabolite composition in the development of MS and the possible mechanisms of the crosstalk between gut microbiota and mitochondrial function in the progression of MS, to provide new therapeutic approaches for the prevention or reduction of MS based on this crosstalk.